Cholesterol in mild cognitive impairment and Alzheimer’s disease in a birth cohort over 14 years - Toro, Pablo; Degen, Christina; Pierer, M.; Gustafson, D.; Schröder, Johannes; Schönknecht, Peter (European archives of psychiatry and clinical neuroscience, 2014)
Animal epidemiological and clinical studies suggest that cholesterol is a risk factor for Alzheimer’s disease (AD). Nevertheless, the relation of cholesterol to mild cognitive impairment (MCI), influence of APOE genotype and its changes in lifespan is controversial. We investigated the potential impact of plasma total cholesterol (TC) on development of MCI and AD in the interdisciplinary longitudinal study on adult development and aging, a representative birth cohort (born 1930-1932), examined in 1993/1994 (VT1), 1997/1998 (VT2), and 2005/2007 (VT3). Of 500 participants at baseline, 381 survived and were examined at VT3. After exclusion of participants with lifetime prevalence of major psychiatric diseases or mild cognitive disorder due to a medical condition, 222 participants were included in the analysis. At VT3, 82 participants had MCI, 22 participants had AD, and 118 were in good health. Participants with MCI and AD at VT3 evidenced higher TC levels at VT1 than those who were healthy. Higher TC levels at baseline were associated with an increased risk for cognitive disorders at VT3 (highest vs. lowest quartile: OR 2.64, 95 % CI 1.12-6.23, p < 0.05). Over the 14 year follow-up, TC levels declined in those with MCI and AD, but remained stable in those who remained healthy. These findings were not modified by APOE genotype or use of cholesterol-lowering medications. Our findings demonstrate that higher TC levels are observed long before the clinical manifestation of MCI and AD in patients without psychiatric or somatic comorbidities and are independent of APOE genotype.
Published online: 17 November 2013
Gesehen am 16.09.2020